Incidentally detected retrosternal goitre with posterior mediastinal extension causing compression of airway: a case report - Paramasivam, Praveen K.; Mohan, Raj; Sahu, P. K.; Keishing, Chuimei; Yadav, Mukesh K.; Varghese, Jeenu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Retrosternal goitre (RG) is an enlarged thyroid gland which extends below the clavicle and sternum. Most patients have slow-growing enlargement without any symptoms but may develop symptoms related to compression of aerodigestive tract like dyspnoea, choking, sleep disturbance, dysphagia and hoarseness. Surgical removal is the treatment of choice either through a cervical approach or combination with sternotomy or thoracotomy. Here we present a case of a 51 years female without any symptoms, detected incidentally to have mediastinal mass on imaging during routine health checkup. On evaluation, she was found to have no significant neck swelling or any evidence of vascular obstruction or neurological compression. Contrast enhanced computed tomography showed large heterogeneous mass lesion extending from posteroinferior aspect of (right) thyroid lobe extending into mediastinum till tracheal bifurcation. Due to the mediastinal extension, multispecialty team approach involving oncosurgeon, ear nose and throat (ENT) surgeon and cardiothoracic surgeon was done. The patient underwent (R) hemithyroidectomy with excision of posterior mediastinal component through combined cervical and mediastinal approach under general anaesthesia. Histopathological examination revealed adenomatous goitre. Post operatively patient was symptom free and is on regular follow-up.